SSR mitigation in power system with static synchronous series compensator - A. Patel, Nilaykumar; Praghnesh Bhatt, Dr (International Journal of Engineering and Technology, 2018)
Series compensation in transmission line with fixed series capacitor may cause Subsynchronous Resonance (SSR) at certain compensation level. This paper presents the application of static synchronous series compensator (SSSC) to mitigate impact of SSR. For analysis of SSR, IEEE first benchmark model is used and SSSC is located in transmission line at generator end. The linearized state space equation of SMIB system without and with SSSC has been developed to carry out eigenvalue analysis to identify potential modes for SSR. The AVR and PSS in the generator control loop coordinated with SSSC can successfully mitigate SSR. Time domain simulation is also carried out to confirm the results obtained with eigenvalue analysis.Â Â